Analysis of professional activity of engineers in the mechanical engineering industry in the context of modern requirements - Kovalskaya, V. (Problems of Engineer-Pedagogical Education, 2019)
The article is dedicated to the analysis of professional activity of engineers in the mechanical engineering industry in the context of modern requirements, and determines the subject, features and means of engineering activity. The paper provides a list of positions that can be occupied by engineers of the mechanical engineering industry, which includes a design engineer, a process engineer, an engineer for the automation and mechanization of production processes, an engineer for automated production management systems. The article characterizes their professional responsibilities and highlights generalized types of ones, and also establishes the necessity of their economically contextual realization as a condition for compliance with the modern realities of the development of the world industry. The paper determined the need to integrate the engineering and economic components of the professional training of future engineers in the mechanical engineering industry, where the levels of integration are a formal combination of engineering and economic activities; logical and substantive integration of engineering and analytical and economic activities; value-semantic integration of economic and engineering strategies. engineering activity, namely design, production, technological, organizational, managerial, and research